Nocardia farcinica masquerading as intracerebral metastases in advanced metastatic prostatic cancer. Issue 9 (7th September 2020) - Livings, Claire; Uemura, Mayu; Patel, Reena; Afshar, Mehran
Abstract : A 67-year-old man with metastatic prostate cancer and underlying asymptomatic pancytopenia presented with a 1-week history of general malaise, left leg weakness and facial numbness. Initial brain imaging demonstrated two rim-enhancing lesions felt to represent intracerebral metastasis. Following neurosurgical referral, a multidisciplinary meeting decision was made for best supportive care and dexamethasone was given. He developed multiple cutaneous lesions, which on incision and drainage revealed Nocardia farcinica . Repeat brain imaging showed enlargement of the existing cavitating lesions and appearance of new lesions, now typical of cerebral abscesses. A diagnosis of disseminated nocardiosis with cutaneous and intracerebral infection was reached. He started taking empirical treatment with intravenous meropenem, co-trimoxazole and subsequent addition of amikacin, with little improvement. On further review of sensitivities, moxifloxacin was added. Following over 1 month of antimicrobial treatment, his neurological symptoms, cutaneous lesions and repeat MRI of the brain had improved.